HIV risk perception and behavior among medically and traditionally circumcised males in South Africa - N. P. Zungu; L. C. Simbayi; M. Mabaso; M. Evans; K. Zuma; N. Ncitakalo; S. Sifunda (BMC, 2016)
Abstract Background In South Africa, voluntary medical male circumcision (VMMC) has recently been implemented as a strategy for reducing the risk of heterosexual HIV acquisition among men. However, there is some concern that VMMC may lead to low risk perception and more risky sexual behavior. This study investigated HIV risk perception and risk behaviors among men who have undergone either VMMC or traditional male circumcision (TMC) compared to those that had not been circumcised. Methods Data collected from the 2012 South African national population-based household survey for males aged 15 years and older were analyzed using bivariate and multivariate multinomial logistic regression, and relative risk ratios (RRRs) with 95 % confidence interval (CI) were used to assess factors associated with each type of circumcision relative no circumcision. Results Of the 11,086 males that indicated that they were circumcised or not, 19.5 % (95 % CI: 17.9-21.4) were medically circumcised, 27.2 % (95 % CI: 24.7-29.8) were traditionally circumcised and 53.3 % (95 % CI: 50.9-55.6) were not circumcised. In the final multivariate models, relative to uncircumcised males, males who reported VMMC were significantly more likely to have had more than two sexual partners (RRR = 1.67, p = 0.009), and males who reported TMC were significantly less likely to be low risk alcohol users (RRR = 0.72, p < 0.001). Conclusion There is a need to strengthen and improve the quality of the counselling component of VMMC with the focus on education about the real and present risk for HIV infection associated with multiple sexual partners and alcohol abuse following circumcision.